Pengaruh Good Corporate Governance Dan Intellectual Capital Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Property Dan Real Estate Yang erdaftar Di BEI Periode 2021-2024 - Deasy Amelia Anggi Sihombing; Mitha Christina Ginting; Gracesiela Y. Simanjuntak (Politeknik Raflesia Press, 2026)
This study aims to analyze the effect of Good Corporate Governance and Intellectual Capital on firm value with financial performance as an intervening variable in property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from the companies’ annual financial reports. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange. The sample comprises 26 companies observed over the 2021–2024 period. The sampling technique used in this research is purposive sampling. The data analysis techniques applied in this study include descriptive analysis, path analysis, classical assumption tests, the coefficient of determination (R²), t-test (partial test), F-test (simultaneous test), and the Sobel test. All statistical analyses were conducted using SPSS version 26. The results of the study indicate that Good Corporate Governance does not have a significant effect on firm value, while Intellectual Capital has a negative and significant effect on firm value. Good Corporate Governance and Intellectual Capital have a positive and significant effect on financial performance. Financial Performance is unable to mediate the relationship between Good Corporate Governance and Intellectual Capital on firm value. Financial Performance does not have a significant effect on firm value. The Adjusted R-square value of 13.5% indicates that Good Corporate Governance and Intellectual Capital explain 13.5% of the variation in financial performance, while the remaining 86.5% is influenced by other variables outside the research model. Good Corporate Governance, Intellectual Capital, and financial performance explain only 2.5% of the variation in firm value, while the remaining 97.5% is influenced by other factors not examined in this study.